Is heart rate in post-hematopoietic stem cell transplant patients clinically relevant?. Issue 1 (2nd January 2022) - Lopez-Candales, Angel; Mathur, Pankaj; Mounsey, J Paul; Veeraputhiran, Muthu
ABSTRACT: Patients with hematological malignancies undergoing hematopoietic stem cell transplantation (HSCT) have become a critical treatment option in the treatment of many hematological malignancies, myeloproliferative disorders, and some solid tumors. Although HSCT has the potential of offering either a cure or minimizing disease burden while improving overall survival, HSCT is associated with some morbidity and mortality, particularly hypertension, diabetes, dyslipidemia, and renal disease with an increased cumulative incidence of cardiovascular (CVD) complications. Aside from the usual heart failure and arrhythmias, a less described complication is sinus tachycardia. The latter was once considered an innocuous finding in post-HSCT patients and mostly attributed to dehydration, low counts, deconditioning, chemotherapy, and/or infection. However, new data has shown that a number of these post-HSCT patients may harbor inappropriate sinus tachycardia, which can be associated with the eventual development of heart failure if not identified and treated. We believe that discussion of this topic not only is needed to raise awareness of this condition as patients might no longer be under the care of their oncologists but, most importantly, could be seen at any age, and general health practitioners might otherwise not be aware of this literature.